Facilitation of students’ disembedding in an online visual arts and mathematics education program - Mehtap Kus; Nora S. Newcombe (International Journal of STEM Education)
Abstract Background Disembedding is a crucial spatial thinking skill in visual arts and mathematics education. It is important in creating and analyzing artworks by separating a figure from its background, as well as for solving geometric problems where shapes must be viewed from new perspectives. Drawing upon research in psychology, arts, and mathematics education, the present study aimed to facilitate students’ disembedding in an online educational program employing the teaching experiment methodology. This program utilized concrete movement artworks, particularly those by Max Bill. Seven sixth-grade students participated remotely in this program, utilizing GeoGebra Classroom. Main findings The analysis of video data (talks and drawings) and written notes over three sessions revealed that this online educational program, which was designed for the specific context of visual arts and mathematics, offered students opportunities for the individual and group observation of diverse artworks, the tracing of shape contours, and guided attention to new perceptual organizations of shapes through prompting questions. Overall, this had the potential to facilitate students’ disembedding. This overall process challenged students’ initial simplistic shape organizations based on Gestalt principles, leading to the identification of primary and secondary structures, as well as reversible figures. Conclusions/potential implications This research sheds light on the concept of disembedding skills rooted in Gestalt psychology, and its connection to the figure-ground phenomenon observed in both artistic and mathematical contexts. This research offers theoretical and practical contributions. First, it suggests an emerging trajectory of disembedding and proposes methods for nurturing students’ disembedding skills. Second, this study serves as an example for art and mathematics educators in schools and informal learning environments (e.g., art museums) to support students’ spatial thinking. This study contributes to the development of educational programs that facilitate students’ spatial thinking in the context of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education.